A Targeted Review of Open Practices in Special Education Publications. (April 2023) - Cook, Bryan G.; van Dijk, Wilhelmina; Vargas, Isabel; Aigotti, Susan M.; Fleming, Jesse I.; McDonald, Sean D.; Richmond, Cassidi L.; Griendling, Lindsay M.; McLucas, Alan S.; Johnson, Rachelle M.
Open practices, such as preregistration, registered reports, open materials, open data, open analytic code, replication, open peer review, open access, and conflict-of-interest and funding statements, support the transparency, accessibility, and reproducibility of research and other scholarship. The purpose of this review was to examine the prevalence of these open practices in the special education literature. We reviewed a randomly selected sample of 250 articles published in special education journals in 2020. Results indicated that conflict-of-interest and funding statements were present in most articles; a small but meaningful proportion of articles provided open materials and were open access; and preregistration, registered reports, open data, open analytic code, open peer review, and replication were rarely or never observed. Recommendations for researching and supporting the use of open practices in special education scholarship are provided.